Biological synthesis of gold nanoparticles by Thermus scotoductus SA-01 - Van Marwijk, Jacqueline (University of the Free State, 2010)
The usual strategy to prepare gold nanoparticles involves the reduction of a gold salt in solution by various reducing agents in the presence of a stabilizer. These particles are mostly spherical with poor monodispersity. An alternative means is to use biological material to mediate particle synthesis. Microorganisms such as fungi have demonstrated the ability to produce nanoparticles of different shapes and sizes extending beyond the scope of chemical means, and the microbial interaction with metals also supply eco-friendly methods for nanoparticle production. It has been hypothesized that the proteins involved in nanoparticle synthesis require a co-factor such as NADH / NADPH, as previous studies have indicated that NADH- and NADPH-dependent enzymes are important factors in the biosynthesis of metal nanoparticles. Thermus scotoductus SA-01, a thermophilic bacterium, isolated from an AngloGold Ashanti mine near Carletonville, Republic of South Africa, was used for purification of a gold(III) reducing and nanoparticle synthesizing protein. This bacterium has the ability to produce gold nanoparticles, and more than one pathway can be followed to produce these particles. A protein was purified to homogeneity by using a combination of several liquid chromatography resins. The N-terminal sequence was obtained by using automated Edman degradation. The protein purified is not a classical oxido-reductase and was identified as an ABC transporter peptide-binding protein (~70kDa). This discovery shows that gold nanoparticles can be produced by proteins other than oxidoreductases. The interaction of the protein extracted and purified from Thermus scotoductus SA-01, as well as the recombinant proteins, with liquid gold under varying physico-chemical conditions have been studied using TEM, EDS, and by measuring the plasmon resonance band, to illustrate the effect on particle morphology and to elucidate the protein mechanism. The size and the shape of particles could, to an extent, be manipulated by controlling the environmental parameters. The purified protein as well as the recombinant proteins was only able to produce nanoparticles in the presence of sodium dithionite and it is thus hypothesized that the donation of electrons via the disulphide bridge in the protein is involved in the reduction of the gold ions. Even though the recombinant proteins had the ability toproduce nanoparticles they were not as efficient as the native protein, but when the optimum parameters for the recombinant proteins are established they could be used in the upscale production of gold nanoparticles or gold nanosheets.

Die algemeenste strategie vir die voorbereiding van nanopartikels behels die reduksie van ŉ opgeloste goudsout deur verskeie reduseermiddels in die teenwoordigheid van ŉ stabiliseerder. Hierdie partikels is meestal sferies met lae monodispersiteit. ŉ Alternatiewe manier om partikels te vorm is om biologiese materiaal te gebruik. Mikroörganismes, soos fungi, beskik oor die vermoeë om nanopartikels van verskillende vorme en groottes te produseer, wat ŉ verbetering is op die gebruik van chemiese metodes. Hierdie mikrobiese interaksie met metale verskaf ook ŉ omgewingsvriendelike metode vir die produksie van nanopartikels. Vorige studies het getoon dat NADH- en NAD(P)H- afhanklike ensieme belangrike faktore is in die biosintese van metaal nanopartikels. Dit het gelei tot die hipotese dat proteïene wat betrokke is by goud nanopartikel sintese ŉ kofaktor soos NADH / NAH(P)H benodig. ŉ Proteïen wat in staat is om goud te reduseer en nanopartikels te vorm, is gesuiwer vanuit die termofiele bacterium, Thermus scotoductus SA-01. Hierdie bakterium was geïsoleer vanuit ŉ AngloGold Ashanti myn naby Carletonville, Republiek van Suid-Afrika en het die vermoeë om goud nanopartikels te produseer deur meer as een biologiese weg te volg. Die proteïen is gesuiwer deur gebruik te maak van ŉ kombinasie van verskeie vloeistofchromatografie harse. Die N-terminale proteïen volgorde is verkry deur gebruik te maak van Edman degradering. Die gesuiwerde proteïen is nie ŉ klasieke oksido-reduktases nie, maar is geïdentifiseer as ŉ ABC transporter-peptied-bindings proteïen (~70kDa). Hierdie ontdekking wys dat goud nanopartikels geproduseer kan word deur ander proteïene as oksido-reduktases. TEM, EDS en die meeting van die plasmon resonans band is gebruik om die effek van variërende fisiese-chemiese kondisies op partikel morfologie te toon en om die proteïen meganisme op te klaar. Vir die doel is die gesuiwerde proteïen vanuit Thermus scotoductus SA-01 asook rekombinante proteïene gebruik. Die grootte en vorm van die partikels kon tot ŉ mate gemanipuleer word deur omgewingsfaktore te beheer. Die gesuiwerde proteïen asook die rekombinante proteïene kon slegs nanopartikels produseer in die teenwoordigheid van natriumdithionaat en ŉ hipotese is geformuleer dat die disulfied brug in die proteïen betrokke is by die reduksie van die goud ione. Alhoewel die rekombinante proteïene oor die vermoeë beskik om nanopartikels te produseer is dié nie so effektief soos die gesuiwerde proteïen nie. Indien die optimale kondisies vir die rekombinante proteïene uitgeklaar word, sal dié waarskynlik in die grootskaalse produksie van goud nanopartikels of goud nanoplate gebruik kan word.
Keywords: Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University Free State, 2010; Nanoparticles -- Synthesis; Nanostructured materials; Proteins; ABC transporter; Nanobiotechnology; Gold; Biological reduction; Metal nanoparticles